(untitled) (Research, Society and Development, 2023)
The study aims to characterize the clinical and epidemiological profile of reported cases of Tuberculosis in the municipality of Macapá from 2014 to 2018. This is a descriptive, cross-sectional and analytical epidemiological study, carried out from secondary data. The study presents the new diagnosed cases of Tuberculosis, which were 886 new cases reported in the period, with an average annual incidence rate of 44.54/100,000 inhabitants, in addition to an average annual mortality rate of 0.6/100,000 inhabitants. . The profile of the disease is also exposed by sex, race, age group, education, in addition to the clinical form and diseases, exams and the clinical evolution of the cases. The study showed a trend towards a quantitative decline in cases, with a concentration of new cases in older age groups over the years, and a decrease in mortality from the disease at all ages, which points to a better quality of approach to new cases. These observations allow a more accurate population perception about the clinical and epidemiological profile of the disease in a national context, identification of the most vulnerable public and improving health promotion practices with regard to tuberculosis.